2017
DOI: 10.1007/s11064-017-2442-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Biochemical Effects of N-Acetylcysteine in Zebrafish Acutely Exposed to Ethanol

Abstract: Alcohol hangover refers to unpleasant symptoms experienced as a direct consequence of a binge drinking episode. The effects observed in this condition are related to the increase in alcohol metabolites and imbalance in oxidative status. N-acetylcysteine (NAC) is a mucolytic agent and an antidote for paracetamol overdose. Preclinical and clinical studies have shown that NAC is a multi-target drug acting through neuroprotective, antioxidant and neurotrophic mechanisms as well as a glutamate modulator. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Another possible explanation is the difference in strain of zebrafish used; AB strain (Mathur and Guo, 2011) compared to wild-type in our study and others (ex. Rosemberg, 2012;Mocelin et al, 2018;Müller et al, 2017). After 8 days of exposure to 1% ethanol for 20 minutes per day, social…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation is the difference in strain of zebrafish used; AB strain (Mathur and Guo, 2011) compared to wild-type in our study and others (ex. Rosemberg, 2012;Mocelin et al, 2018;Müller et al, 2017). After 8 days of exposure to 1% ethanol for 20 minutes per day, social…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed longer durations of ethanol exposure (1 hour) the anxiolytic effect on behaviour seems to change to an anxiogenic state (Rosemburg et al, 2012;Mocelin et al, 2018). Studies examining chronic ethanol exposure in zebrafish have reported inconsistent results, possibly due to the many different exposures times, duration of exposure, duration of withdrawal, and concentration of ethanol used (da Silva Chaves et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The medium was not changed until 3 dpf. NAC concentration was determined in a pilot study as well as in our previous studies ( Mocelin et al, 2015 , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The upper zone of the tank corresponds in rats and mice protocols to the periphery region of the open-field test. Alterations in time spent and number of crossings to this zone are frequently used as a parameter of anxiety in zebrafish ( Mocelin et al, 2015 ; Giacomini et al, 2016 ; Marcon et al, 2016 ; Mocelin et al, 2017 ; Marcon et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were collected and prepared as previously reported by Mocelin et al (2018) . Specifically, after the ACS fish were anesthetized by immersion in cold water and euthanized by decapitation.…”
Section: Methodsmentioning
confidence: 99%